2022
DOI: 10.7717/peerj.13986
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of HIV-1 Tat modifies gene expression in cultured B cells: implications for the development of B-cell lymphomas in HIV-1-infected patients

Abstract: An increased frequency of B-cell lymphomas is observed in human immunodeficiency virus-1 (HIV-1)-infected patients, although HIV-1 does not infect B cells. Development of B-cell lymphomas may be potentially due to the action of the HIV-1 Tat protein, which is actively released from HIV-1-infected cells, on uninfected B cells. The exact mechanism of Tat-induced B-cell lymphomagenesis has not yet been precisely identified. Here, we ectopically expressed either Tat or its TatC22G mutant devoid of transactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…To detect possible changes in B cell physiology caused by chronic HIV‐1 Tat presence, we performed an RNA‐sequencing of BLAS cell lines and compared the results with the previously published transcriptomes of RPMI8866 cell lines (GSE182538) 17 . As expected, we confirmed that GFP expression did not alter significantly the transcriptome profile of RPMI8866 cells: only 20 upregulated and 60 downregulated genes were identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To detect possible changes in B cell physiology caused by chronic HIV‐1 Tat presence, we performed an RNA‐sequencing of BLAS cell lines and compared the results with the previously published transcriptomes of RPMI8866 cell lines (GSE182538) 17 . As expected, we confirmed that GFP expression did not alter significantly the transcriptome profile of RPMI8866 cells: only 20 upregulated and 60 downregulated genes were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Human EBV‐transformed B lymphoblastoid cell line RPMI8866, freshly EBV‐transformed B lymphoblastoid cell line from healthy donor AS (BLAS), immortalized T cell line Jurkat, Jurkat that stably expresses HIV‐1 Tat (Jurkat‐Tat), EBV‐negative BL cell line Ramos, monocytic THP‐1 cell line, neuroblastoma SH‐SY5Y cell line, human embryonic kidney 293T cell line and their derivatives were used in the study (Table ). Cell lines that stably expressed enhanced green fluorescent protein (EGFP), EGFP‐Tat or EGFP‐TatC22G were produced through lentiviral transduction as described previously 14 . Cells were handled, treated, and stained as described in Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that HIV-1 transactivator protein Tat may play a role in the development of B cell lymphomas and induce MYC-IGH proximity in primary B cells in vitro and in vivo. 37,66 Unlike Zebra, the presence of Tat alone is able to promote MYC-IGH proximity; but despite this difference, the generation of DNA damage within the MYC locus and its MRE11dependent relocalization in the nucleus are observed in both cases. Consistently, DNA DSBs have already been linked to chromatin movement, 21,67,68 either for the search of a recombination partner 69,70 or to join the DNA repair centers.…”
Section: Discussionmentioning
confidence: 98%
“…B cell activation was previously linked to MYC preferential relocation next to IGH, 43 and our results confirm this finding (Figure 1D,E). We have previously demonstrated that HIV‐1 transactivator protein Tat may play a role in the development of B cell lymphomas and induce MYC‐IGH proximity in primary B cells in vitro and in vivo 37,66 . Unlike Zebra, the presence of Tat alone is able to promote MYC‐IGH proximity; but despite this difference, the generation of DNA damage within the MYC locus and its MRE11‐dependent relocalization in the nucleus are observed in both cases.…”
Section: Discussionmentioning
confidence: 99%